Lophomonas isolation in sputum sample at Peru - Moya-Salazar, Jeel (2021)
Lophomonas infection is an emerging parasitic disease causing respiratory infections. After China, Peru is the second country with the highest number of cases. In the bright‑field microscopy evaluation of fresh samples, most of them are incorrectly estimated. Therefore, correct identification using cytological stains is to be supplemented. We report a case of a 29‑year‑old male with typical clinical symptoms of pneumonia, marked eosinophilia, and noninfiltrative pattern in chest X‑ray, who had bronchopulmonary lophomoniasis.